IMPLEMENTASI KEBIJAKAN KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI GURU - Siti Syevila; Rizki Akmalia; Syahfira Amanda; Nurul Anjani Daulay; Fadhil Ahmad Zaki (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study analyzes the various policies implemented by school principals to encourage the improvement of teachers' competencies and reveals the important role of principals in developing teachers' professionalism. Principals are responsible for facilitating training and professional development for teachers, so that they can continuously improve their skills and knowledge. This policy also aims to provide teachers with useful feedback and a working environment that allows them to develop. However, this research also shows that there are problems with implementing the policy. Lack of time for teachers to attend training and limited access to necessary resources are some of the challenges faced. But principals can encourage teachers to learn more and become better with the right policies and support.